Konsep Keluarga Smart (Bahagia) Perspektif Khoiruddin Nasution - Suud Sarim Karimullah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2021)
Family without conflict is one of the effective solutions in building a happy family, but in reality there are still many conflicts that occur between family members which result in the disruption of a comfortable, safe, and happy family life. In conditions like this, the urgency of the connection with Khoiruddin Nasution's thoughts on the smart (happy) family concept he offers to realize the happiness of living in the family. library research is the type in this research by trying to collect all the data obtained from various library literature results that still have relevance to this research. Then, a descriptive-analytic model was carried out by explaining the theory and logic of thought through a contents analysis of Khoiruddin Nasution's thoughts on various works he had with a critical paradigm. This study concludes that the smart (happy) family of Khoiruddin Nasution's perspective is built on awareness among family members about the purpose of a marriage which is also the purpose of life. Then, regarding the smart (happy) family concept proposed by Khoiruddin Nasution, it is in accordance with the family concept described in the Qur'an, as described in Surah Ar-Rum [30] verse 21, At-Tahrim [66] verse 6 and Al-Anfal [8] verses 27-28.